Synthesis, characterization and in vitro analyses of lumefantrine-based pharmacologically active polymer for the treatment of severe malaria - Cromarty, Duncan (University of Pretoria, 2023)
Dissertation (MSc (Pharmacology))--University of Pretoria, 2022.